KAZI MAULIK AND KARAKALPAK LITERARY WRITING (American Journal of Interdisciplinary Research and Development, 2025)
The article examines the life and work of Kazi Maulik Bekmukhamed uli, a great master of the word of Karakalpak literature of the late 19th and early 20th centuries.